2006
DOI: 10.1124/jpet.106.107953
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism-Based Pharmacokinetic-Pharmacodynamic Modeling of the Respiratory-Depressant Effect of Buprenorphine and Fentanyl in Rats

Abstract: The purpose of this investigation was to develop a mechanismbased pharmacokinetic/pharmacodynamic (PK/PD) model to predict the time course of respiratory depression following administration of opioids in rats. The proposed model is based on receptor theory and aims at the separate characterization of biophase distribution and receptor association/dissociation kinetics as determinants of hysteresis between plasma concentration and effect. Individual concentration time courses of buprenorphine and fentanyl were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…By simulation it is shown that following i.v. administration of buprenorphine, the concentrations of norbuprenorphine reach values that are well below the values causing an effect on respiration.Recently, the pharmacokinetic-pharmacodynamic (PK-PD) relationship of buprenorphine for the effect on the respiratory response has been studied in rats and humans (Yassen et al, 2007). In these investigations, buprenorphine has been shown to display ceiling of the respiratory depressant effect, indicating that buprenorphine acts functionally as a partial agonist at the -opioid receptor.…”
mentioning
confidence: 99%
“…By simulation it is shown that following i.v. administration of buprenorphine, the concentrations of norbuprenorphine reach values that are well below the values causing an effect on respiration.Recently, the pharmacokinetic-pharmacodynamic (PK-PD) relationship of buprenorphine for the effect on the respiratory response has been studied in rats and humans (Yassen et al, 2007). In these investigations, buprenorphine has been shown to display ceiling of the respiratory depressant effect, indicating that buprenorphine acts functionally as a partial agonist at the -opioid receptor.…”
mentioning
confidence: 99%
“…Based on weight these doses are more than 10-fold larger than in humans (117,378,772). However, the resultant effect-site concentrations between these two mammalian species appear to differ by less than an order of magnitude.…”
Section: Opioid Effects On Respiratory Neurons In Vivomentioning
confidence: 89%
“…In addition to measurement limitations, pharmacokinetics and pharmacodynamics seem to differ significantly between species for both intravenous anesthetics and opioids and seem subject to allometry (378). As a result, rodents (rats and mice) and other small mammals (rabbits) require much larger single doses (mg/kg) and infusion rates (mg/kg/h) of intravenous agents (61,482,491) and opioids (microgram/kg) (25,117,314,359,361,436,772,774) on a weight basis than larger mammals (dogs) and primates (humans). Finally, it is important to realize that only the free plasma concentrations in the aqueous phase of intravenous anesthetics or opioids seem to be relevant for the clinical effect, not the total plasma concentration.…”
Section: What Are Clinically Relevant Concentrations Of Anesthetics?mentioning
confidence: 98%
See 2 more Smart Citations